2021
DOI: 10.1021/acssuschemeng.1c05965
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Recycling of Rare-Earth Elements from NdFeB Magnet Swarf: Techno-Economic and Environmental Perspectives

Abstract: Rare-earth elements (REEs) are increasingly susceptible to supply risks due to their limited geographical availability and growing demand in clean energy applications such as neodymium-iron-boron (NdFeB) magnets used in electric vehicles and wind turbines. When NdFeB magnets are produced, 6−73% of swarf is generated during the manufacturing steps. This paper presents an innovative technology that utilizes copper nitrate to dissolve REEs in NdFeB magnet swarf and subsequently recovers ∼97% of them as mixed rare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…Selective Bioaccumulation of REE from Nd Magnet Swarf. Even high-grade feedstocks like Nd magnet swarf are of mixed composition and therefore vary in the content of highly valuable REE and associated metals, 47 making selectivity crucial for the development of a successful recovery platform. We determined the precise metal content of the Nd magnet swarf used in our growth and recovery experiments using ICP-MS. Iron was the primary metal component of Nd magnet swarf (68.0% Fe), rendering nonselective leaching and uptake mechanisms insufficient for effective REE bioaccumulation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Selective Bioaccumulation of REE from Nd Magnet Swarf. Even high-grade feedstocks like Nd magnet swarf are of mixed composition and therefore vary in the content of highly valuable REE and associated metals, 47 making selectivity crucial for the development of a successful recovery platform. We determined the precise metal content of the Nd magnet swarf used in our growth and recovery experiments using ICP-MS. Iron was the primary metal component of Nd magnet swarf (68.0% Fe), rendering nonselective leaching and uptake mechanisms insufficient for effective REE bioaccumulation.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Even high-grade feedstocks like Nd magnet swarf are of mixed composition, and therefore vary in the content of highly valuable REE and associated metals, [48] making selectivity crucial for the development of a successful recovery platform. We determined the precise metal content of the Nd magnet swarf used in our growth and recovery experiments using ICP-MS. Iron was the primary metal component of Nd magnet swarf (68.0% Fe), rendering non-selective leaching and uptake mechanisms insufficient for effective REE bioaccumulation.…”
Section: Selective Bioaccumulation Of Ree From Nd Magnet Swarfmentioning
confidence: 99%
“…Kaya et al have reported NdFeB permanent magnet recycling by an alternate route sequential griding, sieving, acid baking, calcination, water leaching to recover Fe 2 O 3 and purify REM and finally REM recovery by ultrasonic spray pyrolysis (Kaya et al 2021 ). Chowdhury et al analyzed the sustainable recycling aspect of NdFeB permanent magnet from a techno-economical-environment perspective (Chowdhury et al 2021 ). Chowdhury et al have investigated the techno-economical aspect of REM recovery by sequential acid-free Cu(NO 3 ) 2 leaching followed by REM recovery as REM oxalate and finally REM oxide valorization by calcination.…”
Section: Review Of Rem Valorization Technologies From Anthropogenic W...mentioning
confidence: 99%